Desire for and barriers to obtaining effective contraception among women experiencing homelessness - Elizabeth Corey; Stephanie Frazin; Samantha Heywood; Sadia Haider (BMC, 2020)
Abstract Background Homelessness is a significant and growing problem in the United States. Women experiencing homelessness face unique challenges as they have high rates of unintended pregnancy. They often face significant barriers to obtaining effective contraception. This study aimed to explore the contraceptive preferences, desire for, and barriers to obtaining effective contraception among women experiencing homelessness. Study design In this cross-sectional study, 54 women experiencing homelessness in Chicago who were at risk for unintended pregnancy were surveyed. Results While 94% of the women experiencing homelessness surveyed desired avoiding pregnancy, most were using the least effective contraceptive methods. Among participants, 80% had health insurance, 75% had a high school diploma, and 90% knew where to obtain birth control. Despite these factors, participants faced barriers to obtaining contraception. One significant barrier was lack of comprehensive contraceptive counseling as 62% report a physician had never counseled them on LARC methods. Approximately half of participants desired or would consider using a LARC in the future. Conclusions Women experiencing homelessness in our study demonstrate significant unmet needs for effective contraception. Women experiencing homelessness would benefit from comprehensive contraceptive counseling and improved access to effective forms of contraception.